HUBUNGAN INFORMASI AKUNTANSI DAN FUNGSI MANAJEMEN (mini riset pada unit kerja BRI kota Manado) - Naukoko, Princilvanno Andreas (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
This research aims to find out the relationship of accounting information with management functions in the work unit BRI at Manado city. Management functions which are analyzed in this research are planning, organizing, actuating, and controling. This research use correlation analysis to measure the relationship between accounting information with management functions. Research shows that there is a strong and significant relationship between accounting information and management function in the work unit BRI at Manado city. Between four management functions are analyzed, the functions of planning and control functions have the strongest links with the accounting information on the Manado city BRI working unit.Â Keywords : Accounting information, manajemen functions.